Critical education leadership and policy scholarship : introducing a new research methodology - Courtney, Steven J.; Armstrong, Paul W.; Mckay, Amanda (Emerald Publishing Limited, 2024)
This landmark publication for critical researchers develops and exemplifies a new methodology for researching education leadership, which Courtney has called Critical Education Leadership and Policy Scholarship (CELP). Building on the work of Helen Gunter, the chapters transform what Gunter identifies as a critical space, with its knowledge-production traditions and typical tools, into a distinctive and novel methodology specifically for investigating the co-constitution of education leadership and policy. Positioned at the intersection of education, policy, and society, the authors focus on a range of contexts from England, Ireland, Australia, and China, theorising the interrelationship between education leadership and policy whilst showcasing the advancement of a new methodology for exploring education leadership from a critical perspective. Topics discussed include how school leaders are navigating mistrust in politics, barriers faced by women leaders in HEIs in China, and the responsibility of educational leaders to establish a culture of care in their institutions. Bringing together internationally emerging scholars with leading researchers from within the fields of educational leadership and policy, Critical Education Leadership and Policy Scholarship includes an Afterword by Emerita Professor Helen Gunter.
Keywords: Educational leadership.; Education and state.; Education -- Research -- Methodology.; Education -- Leadership.; Educational strategies and policy: inclusion.; Educational strategies and policy.; elektronické knihy; electronic books